Phosphocreatine Improves Cardiac Dysfunction by Normalizing Mitochondrial Respiratory Function through JAK2/STAT3 Signaling Pathway In Vivo and In Vitro. (30th November 2019) - Qaed, Eskandar; Wang, Jiaqi; Almoiliqy, Marwan; Song, Yanlin; Liu, Wu; Chu, Peng; Alademi, Sawsan; Alademi, Maria; Li, Hailong; Alshwmi, Mohammed; Al-Azab, Mahmoud; Ahsan, Anil; et al.
Abstract : Diabetic cardiomyopathy (DCM) is one of the common cardiovascular complications in patients with diabetes. Accumulating evidence has demonstrated that DCM is thoroughly related to mitochondrial energy impairment and increases the generation of reactive oxygen species (ROS). Therefore, an ongoing study is developing strategies to protect cardiac mitochondria from diabetic complications, especially from hyperglycemia. Phosphocreatine (PCr) plays a major metabolic role in cardiac muscular cells including intracellular concentration of ATP which affects the activity of the myocardium. We hypothesized that PCr might improve oxidative phosphorylation and electron transport capacity in mitochondria impaired by hyperglycemia in vivo and in vitro. Also, we aimed to evaluate the protective effect of PCr against DCM through the JAK2/STAT3 signaling pathway. The mitochondrial respiratory capacity from rats and H9C2 cells was measured by high-resolution respirometry (HRR). Expressions of proteins Bax, Bcl-2, caspase 3, caspase 9, cleaved caspase 3, and cleaved caspase 9, as well as JAK2/STAT3 signaling pathways, were determined by western blotting. ROS generation and mitochondrial membrane potential (MMP) were measured with fluorescent probes. Type 1 diabetes mellitus was induced in Wistar male rats by a single intraperitoneal injection of streptozotocin (STZ) (80 mg/kg body weight). Our results revealed that PCr possessed protective effects against DCM injury by improving the mitochondrial bioenergetics and by positively exerting protective effects against DCM in vivo and in vitro, not only improving diabetes symptom, resulting in changes of cardiac tissue using hematoxylin and eosin (H&E) stain, but also ameliorating biochemical changes. Moreover, PCr increased Bcl-2, caspase 3, and caspase 9 protein expressions and decreased Bax, cleaved caspase 3, and cleaved caspase 9 expressions as well as the JAK2/STAT3 signaling pathway. In conclusion, PCr improves mitochondrial functions and exerts an antiapoptotic effect in vivo and in vitro exposed to oxidative stress by hyperglycemia through the JAK2/STAT3 signaling pathway. Our findings suggest that PCr medication is a possible therapeutic strategy for cardioprotection.